Investigation of the cytocidal potential of Rhinella jimi skin methanol extracts - Brito, S. V.; Sales, D. L.; Costa, J. G. M.; Rodrigues, F. F. G.; Ferreira, F. S.; Angelico, E. C.; Carvalho, J. E.; Almeida, W. O.; Anjos, L. A. [UNESP]; Coutinho, H. D. M. (Informa Healthcare, 2012)
Context: Amphibian skins have wide variety of biologically active compounds associated with the natural defenses of these animals.Objectives: To study the in vitro anticancer activity of methanol extracts of the skin of Rhinella jimi Stevaux (Anura: Bufonidae).Material and methods: The extract was obtained by cold methanol extraction for 96 h using dried skins (295 mg). The methanol skin extract was dried under reduced pressure, giving a 5.5% yield. In order to test for growth-inhibitory activity, in vitro tests were performed with the following cancer cell lines using concentrations ranging between 0.25-250 mu g/mL of the extract by 48 h: K562 (leukemia), MCF-7 (breast), NCI-ADR (breast with MDR phenotype), UACC-62 (melanoma), NCI460 (lung), PCO3 (prostate), HT-29 (colon), OVCAR (ovary), and 786-0 (kidney).Results: The methanol extract of R. jimi produced a growth inhibition in a dose-dependent manner against the most of the assayed cell lines. In addition to the growth inhibition, the extract induced the cell death in the ovary and colon lines (EC50 0.125 and 0.2 mu g/mL, respectively), demonstrating 100% of inhibition with 2.5 mu g/mL. However, prostate and leukemia cell lines demonstrated less sensitivity, with EC50 of 24 and 235 mu g/mL, respectively. This is the first report about the anticancer activity by natural products from the skin of R. jimi.Conclusions: The methanol extracts of R. jimi significantly affected the growth of several cell lines, demonstrating that these compounds are a potential source of substances that could be utilized in cancer treatments.
Keywords: Amphibians; special metabolites; biodrugs; biodiversity conservation; anticancer activity